Preparation method of nano TiO2 composite fluorescent whitening agent
By preparing nano-TiO2 composite fluorescent whitening agents, the problems of poor water solubility and weak fiber binding ability of existing fluorescent whitening agents are solved, and the effect of improving paper whiteness, UV aging resistance and mechanical properties is achieved.
Patent Information
- Application Number
- CN202411493265.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing triazine amino styrene type fluorescent whitening agent has defects such as poor water solubility, weak binding ability to fiber, and easy loss, which limits its effect in paper use.
By preparing nano-TiO2 composite fluorescent whitening agent, condensation using cyanochloride and 4,4'-diaminodisylene-2,2'-disulfonic acid, nanoparticles were grafted, and diethanolamine and epoxy were used to condensate the nanoparticles. Condensation of chloropropane increases quaternary ammonium and hydroxyl groups, improves hydrophilic properties and fiber binding strength.
It improves the UV aging resistance, light stability and fluorescence intensity of the fluorescent whitening agent, inhibits paper yellowing, and enhances the surface strength and mechanical properties of the paper.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorescent whitening agents, and in particular to a method for preparing a nano-TiO2 composite fluorescent whitening agent. Background Art
[0002] Fluorescent whitening agent is a fluorescent dye, also known as white dye, which is widely used in textile, papermaking, washing powder, soap, rubber, plastic, pigment and paint and other fields. Fluorescent whitening agent is a complex organic compound that can absorb ultraviolet light and reflect blue-purple visible light, supplement the deficiency of purple and blue light in the applied product, and increase the total amount of reflected light to achieve the effect of whitening and increasing the volume. For printing paper, cultural paper and some industrial paper, whiteness is still an important indicator. In order to meet the requirements of paper whiteness, the industry uses chemical bleaching (such as chlorine bleaching or hydrogen peroxide bleaching) on the one hand; on the other hand, physical whitening is used for the direct drop after bleaching to make the paper reach the required whiteness. Commonly used physical whitening is to add fluorescent whitening agent in a certain process of the manufacturing process. Fluorescent whitening agents are a class of complex organic compounds, which are often divided into: diphenylethylene type, o-oxynaphthalenone, azole type nitrogen-containing heterocycle and naphthalene dicarboxamide type according to different chemical structures. The diphenylethylene type fluorescent whitening agents are commonly used in the papermaking industry. Diphenylethylene type fluorescent whitening agents use the principle of optical complementarity to achieve a visual whitening effect.
[0003] Triazine amino diphenylethylene type fluorescent brightener is a typical diphenylethylene type fluorescent brightener. Triazine amino diphenylethylene type fluorescent brightener consists of two parts: a continuous conjugated system containing an aromatic ring and one or more substituents; the former has valence electrons that can be excited by ultraviolet rays, and can be excited to emit fluorescence when the molecule absorbs ultraviolet rays; if the substituents in the molecule are more ideal, the fluorescent properties of the conjugated system can be improved, giving the fluorescent brightener a variety of application properties. However, this type of fluorescent brightener has defects such as poor water solubility, weak ability to bind to fibers, and easy loss, which limits its effect in paper use. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a nano-TiO2 composite fluorescent whitening agent to solve the following technical problems: The existing triazine aminobenzene type fluorescent whitening agents have the defects of poor water solubility, weak fiber binding ability, easy loss, etc.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A preparation method of a nano-TiO2 composite fluorescent whitening agent comprises the following steps: adding cyanuric chloride and acetone into a reaction kettle, controlling the temperature to 0-5 DEG C, stirring and dissolving, blending 4,4'-diaminostilbene-2,2'-disulfonic acid and a NaOH solution and then adding them into the reaction kettle, maintaining the pH value of the system at 5-6 during the adding process, keeping the temperature for reaction for 1-3 hours, adding diethanolamine, controlling the pH value to 7-8, keeping the temperature for reaction for 2-4 hours, controlling the temperature to 70-80 DEG C, adding epichlorohydrin, keeping the temperature for reaction for 2-4 hours, controlling the temperature to 80-90 DEG C, adding aminated nanoparticles, adjusting the pH value to 7-8, rotary evaporation to remove acetone, continuing the reaction for 5 hours, cooling, washing with anhydrous ethanol and acetone, recrystallizing with ethanol, and drying to obtain the nano-TiO2 composite fluorescent whitening agent.
[0006] As a further embodiment of the present invention, the NaOH solution is a 1-5wt% NaOH aqueous solution; the addition ratio of cyanuric chloride, acetone, 4,4'-diaminostilbene-2,2'-disulfonic acid, and NaOH solution is 3.69g:35-100mL:3.70g:22-110mL.
[0007] As a further solution of the present invention: the mass ratio of polycyanuric chloride:diethanolamine is 3.69:2.5-2.7.
[0008] As a further embodiment of the present invention, the mass ratio of diethanolamine to epichlorohydrin is 10:4.4-4.6.
[0009] As a further solution of the present invention: the mass ratio of polycyanuric chloride to amino nanoparticles is 3.69:1-1.5.
[0010] As a further embodiment of the present invention: the preparation method of the amino nanoparticles comprises the following steps: A1: Add nano titanium dioxide, deionized water, and sodium hexametaphosphate into a reactor and disperse them evenly by ultrasonication; mix ammonia water and anhydrous ethanol component 1 and add them into the reactor and disperse them evenly; mix tetraethyl orthosilicate and anhydrous ethanol component 2 and add them into the reactor and disperse them evenly; age at room temperature for 5 hours, centrifuge, filter, wash, and dry to obtain nanoparticles; A2: Add nanoparticles, anhydrous ethanol and deionized water into a reaction kettle and disperse them evenly, add γ-aminopropyltriethoxysilane and disperse them evenly, control the temperature to reflux for 9-12 hours, centrifuge, wash and dry to obtain amino nanoparticles.
[0011] As a further scheme of the present invention: the anhydrous ethanol component 1 and the anhydrous ethanol component 2 in A1 are both anhydrous ethanol; the ammonia water is 25-28wt% ammonia water; the addition ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, ammonia water, anhydrous ethanol component 1, tetraethyl orthosilicate, and anhydrous ethanol component 2 is 1g: 100-150mL: 0.05g: 25mL: 725-750mL: 1-5mL: 20-25mL.
[0012] As a further solution of the present invention: the addition ratio of the nanoparticles, anhydrous ethanol, deionized water, and γ-aminopropyltriethoxysilane in A2 is 1 g: 20-40 mL: 10-20 mL: 2-4 mL.
[0013] Beneficial effects of the present invention: (1) The present application prepares a nano titanium dioxide suspension by ultrasonic dispersion, adds sodium hexametaphosphate as a dispersant, uniformly disperses titanium dioxide in an ethanol solution containing aqueous ammonia, and adds tetraethyl tetrasilicate. After hydrolysis and aging, nano titanium dioxide molecules with silicon dioxide coated on the surface are obtained, namely, nanoparticles. The present application then uses γ-aminopropyltriethoxysilane to perform an amination treatment on the nanoparticles to obtain amination nanoparticles. The present application utilizes cyanuric chloride and 4,4'-diaminostilbene-2,2'-disulfonic acid for a primary condensation to successfully graft cyanuric chloride onto 4,4'-diaminostilbene-2,2'-disulfonic acid; then uses diethanolamine for a secondary condensation to graft tertiary amine groups onto 4,4'-diaminostilbene-2,2'-disulfonic acid, and uses epichlorohydrin for ring-opening grafting during the secondary condensation to graft quaternary ammonium groups onto 4,4'-diaminostilbene-2,2'-disulfonic acid; finally, uses amino nanoparticles for a third condensation to obtain a nano-TiO2 composite fluorescent whitening agent.
[0014] The application adds titanium dioxide to the fluorescent whitening agent, which not only can play a fluorescent whitening role, but also titanium dioxide has a shielding effect on ultraviolet rays and a bonding and film-forming effect on the polymer emulsion, effectively improving the ultraviolet aging resistance of the fluorescent whitening agent. The present application loads silicon dioxide on the surface of nano titanium dioxide, which effectively solves the problem that nano silicon dioxide is easily cross-linked when directly added, resulting in poor emulsion stability and loss of whiteness; and silicon dioxide itself has a strong ability to absorb ultraviolet rays. When added to a fluorescent brightener, it forms a network structure with fluorescent molecules to shield the fluorescent particles; the present application coats the surface of titanium dioxide with silicon dioxide and performs surface functionalization treatment. Under the premise of not affecting the ultraviolet absorption performance of titanium dioxide, the photocatalytic activity of titanium dioxide is reduced, thereby achieving the anti-ultraviolet aging time, and effectively preventing the titanium dioxide from generating highly oxidizing holes and highly reducing photogenerated electrons after absorbing ultraviolet rays, which react with substances such as O2 and H2O on the surface of nanoparticles to generate free radicals with high chemical activity. These free radicals react with polymer materials to break the chemical bonds between molecules, resulting in a decrease in the molecular weight and physical and mechanical properties of the polymer materials, and finally causing the degradation of the materials. The present application combines the characteristics of fluorescent dyes emitting fluorescence and the outer layer matrix of nanoparticles shielding external influences, and grafts nanoparticles onto dye molecules to produce fluorescent nanoparticles with good stability and high luminescence efficiency; the fluorescent brightener prepared by the present application effectively improves the photostability and fluorescence intensity of the fluorescent brightener, has a significant effect in inhibiting the yellowing of paper, and can effectively improve the mechanical properties and waterproof properties of paper such as surface strength.
[0015] (2) This application uses cyanuric chloride and 4,4'-diaminostilbene-2,2'-disulfonic acid for a single condensation to successfully graft cyanuric chloride onto 4,4'-diaminostilbene-2,2'-disulfonic acid; then uses diethanolamine for a secondary condensation to graft tertiary amine groups onto 4,4'-diaminostilbene-2,2'-disulfonic acid, and uses epichlorohydrin for ring-opening grafting during the secondary condensation process to graft quaternary ammonium groups onto 4,4'-diaminostilbene-2,2'-disulfonic acid. The quaternary ammonium groups and hydroxyl groups generated during the preparation of the fluorescent whitening agent of this application effectively improve the hydrophilicity and fiber bonding strength of the fluorescent whitening agent, effectively avoid the poor water solubility and poor fiber bonding of general fluorescent whitening agents, and reduce the occurrence of easy loss of materials. DETAILED DESCRIPTION
[0016] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Example 1 The preparation method of amino nanoparticles comprises the following steps: A1: 5g of nano titanium dioxide, 500mL of deionized water, and 0.25g of sodium hexametaphosphate were added to a reactor and dispersed evenly by ultrasonication. 125mL of 25wt% ammonia water and 3625mL of anhydrous ethanol were mixed and added to the reactor and dispersed evenly. 5mL of tetraethyl orthosilicate and 100mL of anhydrous ethanol were mixed and added to the reactor and dispersed evenly. The mixture was aged at room temperature for 5h, centrifuged, filtered, washed, and dried to obtain nanoparticles. A2: 5 g of nanoparticles, 100 mL of anhydrous ethanol, and 50 mL of deionized water were added to a reactor and dispersed evenly, and 10 mL of γ-aminopropyltriethoxysilane was added and dispersed evenly, and the temperature was controlled to reflux for 9 h, and then centrifuged, washed, and dried to obtain amino nanoparticles.
[0018] Example 2 The preparation method of amino nanoparticles comprises the following steps: A1: 5g of nano titanium dioxide, 500-750mL of deionized water, and 0.25g of sodium hexametaphosphate were added to a reactor and ultrasonically dispersed uniformly. 125mL of 25wt% ammonia water and 3700mL of anhydrous ethanol were mixed and added to the reactor and dispersed uniformly. 15mL of tetraethyl orthosilicate and 110mL of anhydrous ethanol were mixed and added to the reactor and dispersed uniformly. The mixture was aged at room temperature for 5h, centrifuged, filtered, washed, and dried to obtain nanoparticles. A2: 5 g of nanoparticles, 150 mL of anhydrous ethanol, and 70 mL of deionized water were added into a reactor and dispersed evenly, and 15 mL of γ-aminopropyltriethoxysilane was added and dispersed evenly, and the temperature was controlled to reflux for 9 h, and then centrifuged, washed, and dried to obtain amino nanoparticles.
[0019] Example 3 The preparation method of amino nanoparticles comprises the following steps: A1: 5g of nano titanium dioxide, 750mL of deionized water, and 0.25g of sodium hexametaphosphate were added to a reactor and ultrasonically dispersed uniformly. 125mL of 25wt% ammonia water and 3750mL of anhydrous ethanol were mixed and added to the reactor and dispersed uniformly. 25mL of tetraethyl orthosilicate and 125mL of anhydrous ethanol were mixed and added to the reactor and dispersed uniformly. The mixture was aged at room temperature for 5h, centrifuged, filtered, washed, and dried to obtain nanoparticles. A2: 5 g of nanoparticles, 200 mL of anhydrous ethanol, and 100 mL of deionized water were added into a reactor and dispersed evenly, and 20 mL of γ-aminopropyltriethoxysilane was added and dispersed evenly, and the temperature was controlled to reflux for 12 h, and then centrifuged, washed, and dried to obtain amino nanoparticles.
[0020] Example 4 A method for preparing a nano-TiO2 composite fluorescent whitening agent comprises the following steps: 3.69g of cyanuric chloride and 100mL of acetone were added to a reactor, the temperature was controlled at 0°C, and the mixture was stirred and dissolved. 3.70g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 100mL of 1wt% NaOH aqueous solution were mixed and added to the reactor. During the addition process, the pH value of the system was maintained at 5. The mixture was kept warm for 2h. 2.5g of diethanolamine was added, the pH value was controlled at 7, and the mixture was kept warm for 3h. The temperature was controlled at 75°C. 1.1g of epichlorohydrin was added, and the mixture was kept warm for 3h. The temperature was controlled at 85°C. 1-1.5g of the amino nanoparticles prepared in Example 1 was added, the pH value was adjusted to 7, acetone was removed by rotary evaporation, the reaction was continued for 5h, the mixture was cooled, the mixture was washed with anhydrous ethanol and acetone, the mixture was recrystallized with ethanol, and the mixture was dried to obtain a nano-TiO2 composite fluorescent whitening agent.
[0021] Example 5 A method for preparing a nano-TiO2 composite fluorescent whitening agent comprises the following steps: 3.69g of cyanuric chloride and 100mL of acetone were added to a reactor, the temperature was controlled at 0°C, and the mixture was stirred to dissolve. 3.70g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 100mL of 1wt% NaOH aqueous solution were mixed and added to the reactor. During the addition process, the pH value of the system was maintained at 5. The mixture was kept warm for 2h. 2.5g of diethanolamine was added, the pH value was controlled at 7, and the mixture was kept warm for 3h. The temperature was controlled at 75°C. 1.1g of epichlorohydrin was added, and the mixture was kept warm for 3h. The temperature was controlled at 85°C. 1g of the amino nanoparticles prepared in Example 2 was added, the pH value was adjusted to 7, acetone was removed by rotary evaporation, the reaction was continued for 5h, the mixture was cooled, the mixture was washed with anhydrous ethanol and acetone, the mixture was recrystallized with ethanol, and the mixture was dried to obtain a nano-TiO2 composite fluorescent whitening agent.
[0022] Example 6 A method for preparing a nano-TiO2 composite fluorescent whitening agent comprises the following steps: 3.69 g of cyanuric chloride and 100 mL of acetone were added to a reactor, the temperature was controlled at 0°C, and the mixture was stirred to dissolve. 3.70 g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 100 mL of 1 wt% NaOH aqueous solution were mixed and added to the reactor. During the addition process, the pH value of the system was maintained at 5. The mixture was kept warm for 2 h. 2.5 g of diethanolamine was added, the pH value was controlled at 7, and the reaction was kept warm for 3 h. The temperature was controlled at 75°C. 1.1 g of epichlorohydrin was added, the reaction was kept warm for 3 h, the temperature was controlled at 85°C, 1 g of the amino nanoparticles prepared in Example 3 was added, the pH value was adjusted to 7, acetone was removed by rotary evaporation, the reaction was continued for 5 h, the mixture was cooled, the mixture was washed with anhydrous ethanol and acetone, the mixture was recrystallized with ethanol, and the mixture was dried to obtain a nano-TiO2 composite fluorescent whitening agent.
[0023] Comparative Example 1 The preparation method of nanoparticles comprises the following steps: 5 g of nano titanium dioxide, 500 mL of deionized water, and 0.25 g of sodium hexametaphosphate were added to a reactor and ultrasonically dispersed evenly. 125 mL of 25 wt% ammonia water and 3625 mL of anhydrous ethanol were blended and added to the reactor and dispersed evenly. 5 mL of tetraethyl orthosilicate and 100 mL of anhydrous ethanol were blended and added to the reactor and dispersed evenly. The mixture was aged at room temperature for 5 h, centrifuged, filtered, washed, and dried to obtain nanoparticles.
[0024] Comparative Example 2 The preparation method of amino nanoparticles comprises the following steps: 5 g of nano titanium dioxide, 100 mL of anhydrous ethanol, and 50 mL of deionized water were added into a reactor and dispersed evenly, and 10 mL of γ-aminopropyltriethoxysilane was added and dispersed evenly, and the temperature was controlled to reflux for 9 h, and then centrifuged, washed, and dried to obtain amino nanoparticles.
[0025] Comparative Example 3 A method for preparing a nano-TiO2 composite fluorescent whitening agent comprises the following steps: 3.69g of cyanuric chloride and 100mL of acetone were added to a reactor, the temperature was controlled at 0°C, and the mixture was stirred and dissolved. 3.70g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 100mL of 1wt% NaOH aqueous solution were mixed and added to the reactor. During the addition process, the pH value of the system was maintained at 5. The mixture was kept warm for 2h. 2.5g of diethanolamine was added, the pH value was controlled at 7, and the reaction was kept warm for 3h. The temperature was controlled at 75°C. 1.1g of epichlorohydrin was added, the reaction was kept warm for 3h, the temperature was controlled at 85°C, 1g of the amino nanoparticles prepared in Comparative Example 1 was added, the pH value was adjusted to 7, acetone was removed by rotary evaporation, the reaction was continued for 5h, the mixture was cooled, the mixture was washed with anhydrous ethanol and acetone, the mixture was recrystallized with ethanol, and the mixture was dried to obtain a nano-TiO2 composite fluorescent whitening agent.
[0026] Comparative Example 4 A method for preparing a nano-TiO2 composite fluorescent whitening agent comprises the following steps: 3.69g of cyanuric chloride and 100mL of acetone were added to a reactor, the temperature was controlled at 0°C, and the mixture was stirred to dissolve. 3.70g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 100mL of 1wt% NaOH aqueous solution were mixed and added to the reactor. During the addition process, the pH value of the system was maintained at 5. The mixture was kept warm for 2h. 2.5g of diethanolamine was added, the pH value was controlled to 7, and the reaction was kept warm for 3h. The temperature was controlled at 75°C. 1.1g of epichlorohydrin was added, the reaction was kept warm for 3h, the temperature was controlled at 85°C, 1g of the amino nanoparticles prepared in Comparative Example 2 was added, the pH value was adjusted to 7, acetone was removed by rotary evaporation, the reaction was continued for 5h, the mixture was cooled, the mixture was washed with anhydrous ethanol and acetone, the mixture was recrystallized with ethanol, and the mixture was dried to obtain a nano-TiO2 composite fluorescent whitening agent.
[0027] Comparative Example 5 A method for preparing a nano-TiO2 composite fluorescent whitening agent comprises the following steps: 3.69 g of cyanuric chloride and 100 mL of acetone were added to a reactor, the temperature was controlled at 0°C, and the mixture was stirred to dissolve. 3.70 g of 4,4'-diaminostilbene-2,2'-disulfonic acid and 100 mL of 1 wt% NaOH aqueous solution were mixed and added to the reactor. During the addition, the pH value of the system was maintained at 5. The mixture was kept warm for 2 h. 2.5 g of diethanolamine was added, the pH value was controlled to 7, and the reaction was kept warm for 3 h. The temperature was controlled at 85°C. 1 g of the amino nanoparticles prepared in Comparative Example 1 was added, the pH value was adjusted to 7, acetone was removed by rotary evaporation, the reaction was continued for 5 h, the mixture was cooled, washed with anhydrous ethanol and acetone, recrystallized with ethanol, and dried to obtain a nano-TiO2 composite fluorescent whitening agent.
[0028] Performance Testing (1) UV aging resistance a: Preparation of test samples: Take poplar APMP (alkaline hydrogen peroxide mechanical pulp) and deionized water to make a 10wt% solution, add 0.05% EDTA, 1% H2O2, 0.5% Na2SiO3, adjust the pH value to 10 with EDTA, then keep it at 70℃ for 90min, wash the pulp with deionized water several times, squeeze out the water. Add the pulp to the sheet machine, and the content of the sheet is 100g / m 2 A circular paper sample is prepared, the paper sample is cut into 80 mm × 80 mm paper pieces, 10% oxidized starch solution is added, and after gelatinization at 90° C. for 30 min, the solid content is adjusted to 4%, and then the nano-TiO2 composite fluorescent brightener prepared in Examples 4-6 and Comparative Examples 3-5 is added to prepare a sizing solution, the paper is coated on a coating machine, and the paper is dried in the dark; b: Testing steps: After the paper sample is air-dried, place it in a UV aging box for UV aging test. The output power of the UV aging box is 5.3mW / cm 2 , the temperature was set to 25℃, the wavelength of the UV lamp was 340nm, the paper sample was laid flat in the box, and the light was irradiated for 40h, and the whiteness was tested by YQ-Z-48B whiteness meter; the test results are shown in Table 1; Table 1 Statistical table of anti-ultraviolet performance test data of Examples 4-6 and Comparative Examples 3-5
[0029] As can be seen from Table 1, the nano-TiO2 composite fluorescent brightener prepared in the present application is added to paper processing, which effectively reduces the yellowing rate of paper after ultraviolet treatment, has excellent anti-ultraviolet aging performance, and is used in paper processing, with high light stability and high fluorescence intensity.
[0030] (2) Tensile strength and bursting index: The nano-TiO2 composite fluorescent brightener prepared in Examples 4-6 and Comparative Examples 3-5 of the present application was coated on the surface of paper (purchased from Changchun Paper Testing Machine Co., Ltd.) (fluorescent brightener addition amount 0.5%), and the tensile strength and bursting index were tested; the test results are shown in Table 2; Table 2: Statistical table of mechanical properties test data of Examples 4-6 and Comparative Examples 3-5
[0031] It can be seen from Table 2 that the nano-TiO2 composite fluorescent whitening agent prepared in the present application has a strong bond with paper fibers and effectively improves the mechanical properties of the material.
[0032] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a nano-TiO2 composite fluorescent whitening agent, characterized in that: The method comprises the following steps: adding cyanuric chloride and acetone into a reaction kettle, controlling the temperature to 0-5 DEG C, stirring and dissolving, blending 4,4'-diaminostilbene-2,2'-disulfonic acid and NaOH solution and adding the mixture into the reaction kettle, maintaining the pH value of the system at 5-6 during the adding process, keeping the temperature for reaction for 1-3 hours, adding diethanolamine, controlling the pH value to 7-8, keeping the temperature for reaction for 2-4 hours, controlling the temperature to 70-80 DEG C, adding epichlorohydrin, keeping the temperature for reaction for 2-4 hours, controlling the temperature to 80-90 DEG C, adding aminated nanoparticles, adjusting the pH value to 7-8, removing acetone by rotary evaporation, continuing the reaction for 5 hours, cooling, washing with anhydrous ethanol and acetone, recrystallizing with ethanol, and drying to obtain a nano-TiO2 composite fluorescent whitening agent.
2. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 1, characterized in that: The NaOH solution is a 1-5wt% NaOH aqueous solution; the addition ratio of cyanuric chloride, acetone, 4,4'-diaminostilbene-2,2'-disulfonic acid, and NaOH solution is 3.69g:35-100mL:3.70g:22-110mL.
3. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 1, characterized in that: The mass ratio of cyanuric chloride:diethanolamine is 3.69:2.5-2.
7.
4. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 3, characterized in that: The mass ratio of diethanolamine:epichlorohydrin is 10:4.4-4.
6.
5. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 3, characterized in that: The mass ratio of cyanuric chloride to amino nanoparticles is 3.69:1-1.
5.
6. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 1, characterized in that: The preparation method of the amino nanoparticles comprises the following steps: A1: Add nano titanium dioxide, deionized water, and sodium hexametaphosphate into a reactor and disperse them evenly by ultrasonication; mix ammonia water and anhydrous ethanol component 1 and add them into the reactor and disperse them evenly; mix tetraethyl orthosilicate and anhydrous ethanol component 2 and add them into the reactor and disperse them evenly; age at room temperature for 5 hours, centrifuge, filter, wash, and dry to obtain nanoparticles; A2: Add nanoparticles, anhydrous ethanol and deionized water into a reaction kettle and disperse them evenly, add γ-aminopropyltriethoxysilane and disperse them evenly, control the temperature to reflux for 9-12 hours, centrifuge, wash and dry to obtain amino nanoparticles.
7. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 6, characterized in that: In A1, both the anhydrous ethanol component 1 and the anhydrous ethanol component 2 are anhydrous ethanol; the ammonia water is 25-28wt% ammonia water; the addition ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, ammonia water, anhydrous ethanol component 1, tetraethyl orthosilicate, and anhydrous ethanol component 2 is 1g: 100-150mL: 0.05g: 25mL: 725-750mL: 1-5mL: 20-25mL.
8. The method for preparing a nano-TiO2 composite fluorescent whitening agent according to claim 6, characterized in that: The addition ratio of nanoparticles, anhydrous ethanol, deionized water, and γ-aminopropyltriethoxysilane in A2 is 1 g: 20-40 mL: 10-20 mL: 2-4 mL.
Citation Information
Patent Citations
Acid resistance type disulfonic acid liquid fluorescent whitening agent preparation method
CN103483868A
Environment-friendly fluorescent whitening agent for papermaking and preparation method thereof
CN109457539A
Cationically modified white pigments, their production and use
CN1411494A